2008
DOI: 10.1093/europace/eun178
|View full text |Cite
|
Sign up to set email alerts
|

Presence of ventricular dyssynchrony and haemodynamic impact of right ventricular pacing in adults with repaired Tetralogy of Fallot and right bundle branch block

Abstract: Some TOF adults with RBBB exhibit biventricular electromechanical dyssynchrony. However, in symptomatic patients with RV dysfunction, atrio-synchronized RV pacing does not induce significant acute haemodynamic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…1,2 Similarly, right bundle branch block (RBBB) is common, and prolonged QRS duration conveys risk for adverse outcome. 3 Although electromechanical abnormalities are recognized in this population, 2,[4][5][6] specific patterns of regional mechanical abnormalities induced by abnormal electric activation associated with RBBB have not been studied. In left bundle branch block (LBBB), abnormal electric activation leads to a typical mechanical dyssynchrony pattern characterized by early septal activation, observed echocardiographically as a septal flash, with concomitant lateral wall prestretch and late contraction of the early-stretched lateral wall.…”
mentioning
confidence: 99%
“…1,2 Similarly, right bundle branch block (RBBB) is common, and prolonged QRS duration conveys risk for adverse outcome. 3 Although electromechanical abnormalities are recognized in this population, 2,[4][5][6] specific patterns of regional mechanical abnormalities induced by abnormal electric activation associated with RBBB have not been studied. In left bundle branch block (LBBB), abnormal electric activation leads to a typical mechanical dyssynchrony pattern characterized by early septal activation, observed echocardiographically as a septal flash, with concomitant lateral wall prestretch and late contraction of the early-stretched lateral wall.…”
mentioning
confidence: 99%
“…Any additional contribution of the initial hypoxemia and genetic alterations to the development of late left and right ventricular dysfunction or arrhythmias are not accounted for in this condition [24,25]. The model, nevertheless, closely reproduced the electrophysiologic and mechanical abnormalities found in patients with this disorder, including the delayed development of the right bundle branch block [8,9,19]. The animals developed QRS widening as they aged as seen in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical repair of TOF is highly successful, though may be later complicated by right ventricular dysfunction due to volume and pressure overload and by late sudden death. The incompletely understood mechanisms of these delayed adverse developments may be partially due to the surgically-induced permanent right bundle branch block (BBB) and ventricular dyssynchrony [4][5][6][7][8][9]. Therapeutic options remain limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with QRS duration greater than 180 ms have been shown to have significant intraventricular delay and abnormal strain patterns by vector velocity imaging as well as decrease in left ventricular ejection fraction [34]. Attempts to optimize more traditional pacing modalities have shown that, if RV dysfunction has already become apparent, no acute hemodynamic benefit is seen with purely atrioventricular synchronized RV pacing [35]. It is possible, however, to normalize the QRS duration in some patients with Tetralogy of Fallot by adjusting the atrioventricular delay [36].…”
Section: Adults With Congenital Heart Diseasementioning
confidence: 99%